Survey Study on Common Knowledge and Practices of Medicinal Value of Seaweeds in the Southern Coastal area of Sri Lanka - Herath, H.M.K.C.; De Silva, R.H.S.K. (Faculty of Indigenous Medicine, University of Colombo, 2025)
Seaweeds are considered as a sustainable resource in health industry. Many countries are using seaweeds for medicinal purposes due to their high nutrient content. As there is a high abundance of seaweeds in the coastal area of Sri Lanka, possibilities of using seaweeds by community is high. The survey study was conducted to assess the awareness, attitude and practices of the medicinal value of seaweeds among the communities in the Southern coastal area of Sri Lanka. This quantitative, Cross sectional survey study was carried out on 41 participants in Galle, Matara and Hambanthota districts mainly from fishermen, divers, traditional practitioners using purposive sampling for two months. Data were collected through an interview using questionnaire including 05 Questions for awareness, 03 for practices and usage and 02 for attitude and filled by principal investigator. Data were entered into SPSS and descriptive statistics were carried out. Among 41 participants, 29 were males and 12 were females. 82.9% have a good awareness, 70.7% were used seaweed for medicinal purposes and 61% were experienced the effectiveness (A total 68.3% were unaware about the side effects of seaweeds). Study revealed seaweeds were used for skin conditions like acute wounds and burns, thyroid dysfunctions, joint diseases, as an immunity booster and digestive issues like diarrhea. The study revealed that in the Southern coastal area, there is high awareness, usage and practices and positive attitude about medicinal value of seaweeds emphasizing the need for greater research, education, and conservation efforts to ensure the sustainable and effective use of this natural resource.
Keywords: Seaweeds; Awareness; Attitude; Practices; Medicinal value